Chronic Pain Assessment in the Elderly - Ruangritchankul, Sirasa; Krairit, Orapitchaya (Research Medical Journal, 2018)
Most elderly population suffer from chronic pain which lasts for more than three months. Chronic pain has an effect on physical and psychological status as well as caregivers. Pathophysiology of chronic pain comprises four categories including nociceptive pain, neuropathic pain, mixed pain, and psychological pain. Chronic pain has negative impact on physical health such as tachycardia, hypertension, anorexia, and sleep disturbance; and on psychological health including depression and anxiety. The elderly with chronic pain are evaluated by physicians and nurses in terms of taking histories, physical examination, and applying pain assessment tools to identify severity of pain. Choice of pain assessment tools for older adults is based on individual such as cognitive function and communication skills. However, many physicians cannot precisely evaluate pain among the elderly due to visual, auditory, and cognitive impairment, leading to obstacles in communication and assessment. The best chronic pain assessment tool is multidimensional tool which can accurately identify severity and types of pain. The most common used multidimensional tool in practical is short-form McGill pain questionnaire (SF-MPQ). However, multidimensional tool is only appropriate in the elderly without communication problems and cognitive impairment.